Assessment of Intraoperative Blood Loss during Oral and Maxillofacial Surgical Procedures in a Nigerian Tertiary Health Care Center. (2nd September 2014) - Akinbami, Babatunde O.; Onajin-Obembe, Bisola
Abstract : Background . Reports on estimated amount of blood loss in maxillofacial surgical procedures will guide clinicians through units of blood required for each procedure. The aim of the study was to assess the amount of blood loss and duration of surgery. Methods . All cases of maxillofacial surgical procedures done under GA in the MFU theatre, from January 2007 to December 2013, were included in the study. Pre- and postoperative haematocrit values, number of units of whole blood requested and used, amount of blood loss, and duration of surgery were recorded. Results . 139 patients were analyzed, of which 75 (54.0%) were males and 64 (46.0%) were females. Fifty-six (40.3%) cases involved soft tissues. Eighty-three cases involved hard tissues. Age range was 2 months to 78 years; mean ± (SD) was 21.3 ± ( 18.5 ) years. Isolated unilateral cleft lip had the lowest mean value of estimated blood loss of 10.4 ± 10.8 mLs and also the lowest duration of surgery of 58 (76) minutes. There was no significant relationship between both parameters for cleft lip. Fractures of the mandible had mean blood loss of 352 mLs and duration was 175 min. Conclusion . In this study, there was significant relationship between estimated blood loss and duration of surgery for mandibular and zygomatic complex fractures.